The acceptability of homebased exercise snacking and Tai-chi snacking amongst high and low function UK and Taiwanese older adults - Liang, Ian Ju; Francombe-Webb, Jessica; McGuigan, Polly M.; Perkin, Oliver J.; Thompson, Dylan; Western, Max J. (Frontiers in Aging, 2023)
Exercise 'snacking' and Tai-chi 'snacking' protocols are designed to overcome typical barriers to older adults' participation in muscle strength and balance exercise, using short bouts of home-based exercise. This study aimed to investigate the acceptability of homebased exercise-and Tai-chi snacking in British and Taiwanese older adults of high and low physical function. Thirty-three British and Thirty Taiwanese older adults took part in semi-structured interviews, after trying oneweek of exercise-and Tai-chi snacking. The interview schedule and deductive framework analysis was based on the seven components of the Theoretical Framework of Acceptability (TFA). Differences between the Taiwanese and UK participants and those considered high versus low physical function were also analysed. Both snacking regimes were found to be convenient and easy to implement. Participants reported that no activity had to be given up, and considered the programmes would be beneficial to their physical and mental health. Interestingly, more UK-based participants preferred the elegant and relaxing movements of Tai-chi snacking, yet participants with low physical function experienced difficulties when mastering Tai-chi movements. A few high physical function participants perceived exercise snacking to be tedious. Overall, the snacking exercise was found to be acceptable and useful. Personal affective attitude and different cultural backgrounds may affect exercise participation. Nevertheless, it is important to consider individuals' physical function when designing exercise regime. The findings indicate that making Tai-chi snacking easier to master initially, building in progression and adding some upper body movements in the exercise snacking may further enhance acceptability.